1995
DOI: 10.1177/0272989x9501500204
|View full text |Cite
|
Sign up to set email alerts
|

The Covariance Decomposition of the Probability Score and Its Use in Evaluating Prognostic Estimates

Abstract: The probability score (PS) or Brier score has been used in a large number of studies in which physician judgment performance was assessed. However, the covariance decomposition of the PS has not previously been used to evaluate medical judgment. The authors introduce the technique and demonstrate it by analyzing prognostic estimates of three groups: physicians, their patients, and the patients' decision-making surrogates. The major components of the covariance decomposition--bias, slope, and scatter--are displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…A strong emotional fear of cancer and the desire for an urgent peace of mind can lead to a rash decision about screening when it is presented as an immediate option. Patients may also have difficulty assessing probabilities, and as a result are often overly optimistic about their own outcome when faced with the probabilities of survival with treatment options [36] and overestimate their risk of disease. For example, it has been reported that some men overestimate their lifetime risk of developing and dying from prostate cancer [37].…”
Section: Discussionmentioning
confidence: 99%
“…A strong emotional fear of cancer and the desire for an urgent peace of mind can lead to a rash decision about screening when it is presented as an immediate option. Patients may also have difficulty assessing probabilities, and as a result are often overly optimistic about their own outcome when faced with the probabilities of survival with treatment options [36] and overestimate their risk of disease. For example, it has been reported that some men overestimate their lifetime risk of developing and dying from prostate cancer [37].…”
Section: Discussionmentioning
confidence: 99%
“…We anticipate that the observed and predicted occurrence of PrUs will be similar across the risk groups. A perfect calibration (ie, perfect agreement between the predicted and observed outcomes) will produce a calibration line with an intercept and slope of 0 and 1, respectively [ 27 - 29 ]. The smooth curve will be added to reveal differential calibration among risk deciles, if present.…”
Section: Methodsmentioning
confidence: 99%
“…Accuracy will be assessed with Nagelkerke’s R 2 47 and the Brier score. 48 Discrimination will be assessed using the concordance statistic. Model calibration is especially important in the development of prognostic models, as probabilities of future risk are of primary interest.…”
Section: Methods and Analysismentioning
confidence: 99%